Indah Laundry / Ezrin Mohamad...[et al.] - Mohamad, Ezrin; Dabal, Titien Irdianawaty; Mohd Tamrin, Herdawaty; Ali, Artisafarida; Amat Dusia, Kathyrina (Faculty of Business Management, 2001)
According to this title, we have chosen to provide laundry services. Therefore, we have named our business as lndah Laundry. Our business initial cash capital RM 122,500 contributed by all business partners and one from our partners contributed fixed capital (computer) amounted RM2500. We also chose a strategic location at Taman lndah Permai. The nature of the business will be expended is the business have good perfonnance.